2020
DOI: 10.1029/2020ea001267
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling Satellite Retrieved Soil Moisture Using Regression Tree‐Based Machine Learning Algorithms Over Southwest France

Abstract: Satellite retrieved soil moisture (SM) shows great potential in hydrological, meteorological, ecological, and agricultural applications, while the coarse resolution limits its utilization in regional scale. The regression tree-based machine learning algorithms reveal promising capability in SM downscaling. However, it lacks systematic study dedicated to intercomparisons of algorithms to explicitly illuminate their characteristics. In this study, comparisons are made to systematically evaluate performances of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 102 publications
3
18
0
Order By: Relevance
“…In general, the performance evaluation results indicated that the RF models developed at both spatial scales for all the experiments showed higher performance measures for the condition of our study area, which was a warm summer humid climate with a predominance of vegetation. This agreed quite well with the results reported by previous studies conducted in different regions of the world under varying climatic and land surface conditions using the RF model, e.g., the subtropical continental monsoon [72], semi-humid temperate monsoon [25], South Asian monsoon [23,62], and Mediterranean climate zone [73].…”
Section: Rf Model Performance Evaluationsupporting
confidence: 92%
“…In general, the performance evaluation results indicated that the RF models developed at both spatial scales for all the experiments showed higher performance measures for the condition of our study area, which was a warm summer humid climate with a predominance of vegetation. This agreed quite well with the results reported by previous studies conducted in different regions of the world under varying climatic and land surface conditions using the RF model, e.g., the subtropical continental monsoon [72], semi-humid temperate monsoon [25], South Asian monsoon [23,62], and Mediterranean climate zone [73].…”
Section: Rf Model Performance Evaluationsupporting
confidence: 92%
“…The overestimated phenomenon is located in the central and northern areas. This is consistent with earlier studies [1,46,59], which illustrate that machine learning methods tend to reduce the range of the target data. Therefore, the method will reduce the value of the high soil moisture area in the original AMSR-E data and increase the value of the low soil moisture area.…”
Section: Difference Between Downscaled Data and Soil Moisture Of Amsr-esupporting
confidence: 91%
“…The other studies which outperformed ours used alternative model calibration and validation strategies ( Table S1 ). For example, random division of calibration and validation datasets was adopted by studies that reported more promising model fits (R 2 > 0.8) ( Liu et al, 2020 ; Greifeneder, Notarnicola & Wagner, 2021 ; Zhang et al, 2021 ). It should be noted that validation against randomly selected data points, even if stratified by study years, can generate much better model fits compared to independent sites because of the use of autocorrelated time-series data for both model training and validation ( Meyer et al, 2018 ; Ploton et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%